Student grievances and discipline matters project : good practice guide for handling complaints and appeals in Australian universities. - Jackson, Jim; Fleming, Helen; Kamvounias, Patty; Varnham, Sally (Southern Cross University, 2009)
Since the mid 1990s, participation in Australian higher education has increased markedly. There has been much speculation about whether there has been a significant increase in complaints, including litigation. Since the establishment of the Australian Universities Quality Agency in 2000, universities have had to turn their attention to improvements in the provision of quality teaching and learning. However, little attention has been paid to establishing any code, set of principles or guidelines in relation to the handling of student grievances and discipline matters. The Student Grievances and Discipline Matters Project commenced in mid-2007. Its purpose was to gain a better understanding of why and how conflicts between students and universities arise and, in some cases, escalate into external complaints or litigation. During 2007 and 2008, the project identified some of the problems that arise in the way universities handle complaints and appeals, and suggested ways in which mechanisms might be improved. Key findings and recommendations are included. [Executive summary, ed]